2011
DOI: 10.1007/s11033-011-0991-z
|View full text |Cite
|
Sign up to set email alerts
|

Diversification, phylogeny and evolution of auxin response factor (ARF) family: insights gained from analyzing maize ARF genes

Abstract: Auxin response factors (ARFs), member of the plant-specific B3 DNA binding superfamily, target specifically to auxin response elements (AuxREs) in promoters of primary auxin-responsive genes and heterodimerize with Aux/IAA proteins in auxin signaling transduction cascade. In previous research, we have isolated and characterized maize Aux/IAA genes in whole-genome scale. Here, we report the comprehensive analysis of ARF genes in maize. A total of 36 ARF genes were identified and validated from the B73 maize gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(53 citation statements)
references
References 65 publications
0
53
0
Order By: Relevance
“…The availability of genomic resources such as ESTs and genome sequences has provided an opportunity to look for the members of ARF gene family. Until now, 23 Arabidopsis ARFs, 25 rice ARFs, 39 poplar ARFs, 13 Physcomitrella patens ARFs, 17 tomato ARFs, 10 Selaginella moellendorfiri ARFs and 22 maize ARFs have been deduced based on genomic resources, respectively (Hagen and Guilfoyle 2002;Wang et al 2007;Kalluri et al 2007;Rensing et al 2008;Kumar et al 2011;Banks et al 2011;Wang et al 2012). Finet et al (2013) also reported the information on ARF gene families in other 15 plant species including 19 ARF genes in grapevine.…”
Section: Resultsmentioning
confidence: 99%
“…The availability of genomic resources such as ESTs and genome sequences has provided an opportunity to look for the members of ARF gene family. Until now, 23 Arabidopsis ARFs, 25 rice ARFs, 39 poplar ARFs, 13 Physcomitrella patens ARFs, 17 tomato ARFs, 10 Selaginella moellendorfiri ARFs and 22 maize ARFs have been deduced based on genomic resources, respectively (Hagen and Guilfoyle 2002;Wang et al 2007;Kalluri et al 2007;Rensing et al 2008;Kumar et al 2011;Banks et al 2011;Wang et al 2012). Finet et al (2013) also reported the information on ARF gene families in other 15 plant species including 19 ARF genes in grapevine.…”
Section: Resultsmentioning
confidence: 99%
“…Genome-wide analyses on the maize reference genome were performed to identify the Aux/IAA (Wang et al, 2010b) and ARF gene families in maize (Liu et al, 2011; Xing et al, 2011; Wang et al, 2012). The 31 identified ZmAux/IAA genes showed a putative expression (based on EST mining) in different tissues and organs that suggests a temporal and spatial pattern of regulation.…”
Section: Hormonal Coordination Of Seed Developmentmentioning
confidence: 99%
“…The 31 identified ZmAux/IAA genes showed a putative expression (based on EST mining) in different tissues and organs that suggests a temporal and spatial pattern of regulation. The 31–36 ZmARF are also known to have a tissue-specificity that changes during plant development (Wang et al, 2010b, 2012; Liu et al, 2011; Xing et al, 2011). Each ZmARF possesses a sister pair due to chromosomal duplication of the maize genome, and they are distributed in all the chromosomes except chromosome 7 (Xing et al, 2011; Wang et al, 2012).…”
Section: Hormonal Coordination Of Seed Developmentmentioning
confidence: 99%
“…Until now, based on reported genomic sequences, 23 ARFs have been identified in Arabidopsis, 25 in rice, 39 in poplar, 13 in Physcomitrella patens, 17 in tomato, 10 in Selaginella moellendorfiri, 36 in maize, 15 in cucumber and 19 in grape (Banks et al 2011;Hagen and Guilfoyle 2002;Kalluri et al 2007;Kumar et al 2011;Liu and Hu 2013a;Rensing et al 2008;Wan et al 2014;Wang et al 2007Wang et al , 2012. It is believed that the multi-member phenomenon of a specific gene family in a particular organism is caused by the frequent emergence of extensive genomic duplication and diversification in the evolutionary history of organisms.…”
Section: Discussionmentioning
confidence: 99%